Chicken soup for the soul : be you : 101 stories of affirmation, determination and female empowerment - Newmark, Amy (Chicken soup for the soul)
You are unique--and that is your superpower. In these 101 stories of affirmation, determination and female empowerment, you'll find role models and advice to help you make the most of that power. You'll learn how they became comfortable in their own s